PWE-110 unvetted pig versus peg service with nutrition support team. have we improved mortality?. (8th June 2018) - Chatten, Kelly; Brennan, Fiona; Donald, Kirsty; Moran, Michelle; Ridings, Emma; McCann, Steven; Burrows, Gillian; Jafar, Wisam
Abstract : Introduction: The 2004 NCEPOD report highlighted the high 30 day mortality following PEG (percutaneous endoscopic gastrostomy) insertion secondary to inappropriate patient selection[1]. This led to the 2010 BSG guidelines which recommended that a designated nutrition support team (NST) should provide a framework for patient selection to reduce unsuitable patients receiving PEGs[2]. Prior to 2013 in Stockport NHS Foundation trust PIGs (per-oral image-guided gastrostomy) were inserted or patients referred to another trust for PEG placement. There was no formalised referral or screening process. Subsequently a nutrition team was appointed with inpatient assessment of patients and MDT for complex cases. Our Aim was to assess whether the implementation of a nutritional team PEG service reduced 30 day all-cause mortality. Methods: Retrospective analysis of electronic patient records for 30 day all-cause mortality for all PIG and PEG insertions between 2013 and 2017. Statistical analysis was performed using chi-squared. Results: 48 patients (2 excluded as paediatric case and no notes available) had a PIG inserted without formal nutrition team review and 135 patients had PEG following nutrition nurse or MDT assessment. The 2 groups were similar with an average age of 79 years (PIG) and 76 years (PEG) and the majority inserted for stroke (62% PIG and 50% PEG). 30 day mortality on the non-vetted PIG group was 17.4% compared to 5.2% in the PEG group. This was statistically significant with p=0.0048 Conclusions: For the unassessed PIG service mortality was similar to that detailed by the NCEPOD report, demonstrating that despite this and BSG guidelines attitudes towards PEG/PIG insertion among non-specialists have not changed since 2004. By introducing an NTS and PEG service mortality has reduced significantly. With an ever increasing ageing population, trends in PEG placement are rising[3]. It is a necessity to ensure that patients are being appropriately assessed to prevent futile procedures. References: . Ponsky JL. Percutaneous Endoscopic Gastrostomy 2004;719 :901–4. doi:10.1016/j.gassur.2003.12.002 . Westaby D, Young A, O'Toole P, et al. The provision of a percutaneously placed enteral tube feeding service. Gut 2010;59 :1592–605. doi:10.1136/gut.2009.204982 . Mendiratta P, Tilford JM, Prodhan P, et al. Trends in percutaneous endoscopic gastrostomy Placement in the Elderly From 1993 to 2003. Am J Alzheimer's Dis Other Dementiasr 2012;27 :609–13. doi:10.1177/1533317512460563